Raíces del Brasil y sus intérpretes, ochenta años después: una crítica historiográfica de la visión democrática y autoritaria de las interpretaciones del ensayo histórico - Machado Bruno, Daniel (Espacio Tiempo y Forma. Serie V, Historia Contemporánea, 2019)
Durante los últimos años, el libro Raíces del Brasil y su autor, Sergio Buarque de Holanda, inscripto en el canon del pensamiento social brasileño como uno de los principales intelectuales pensadores y articuladores de la nación, han recibido por parte de la historiografía aportes en una fortuna crítica que revisita su interpretación y destaca nuevas posibilidades de entender la revisión que el propio autor realizó a partir de la segunda edición del texto, aspecto que, hasta ese momento, estaba al margen de los argumentos políticos movilizados por sus intérpretes de ciencias sociales. Formando parte de ese conjunto de nuevas investigaciones, este artículo tiene el objetivo principal de discutir la producción historiográfico-política contemporánea que se dedica a explicar los cambios introducidos en Raíces del Brasil, problematizando las clasificaciones del texto de acuerdo con las visiones políticas liberal-democráticas, radical-democráticas y, más recientemente, de lecturas que le atribuyen posturas que se aproximan al conservador-autoritarismo de los años 1930. Abstract Sérgio Buarque de Holanda, author of Roots of Brazil, has been interpreted by his critics as one of main intellectual thinkers of the proccess to brazilian national construction. During the last years, his critical fortune revisited the book to start a reevaluation of its political message. In this perspective, the analysts emphasized the need to analyze the author’s revision after the second edition of the text, an aspect that, until that moment, was outside the political arguments mobilized by its interpreters of social sciences. As a part of this set of new research, this article has the main objective of discussing the contemporary historiographic-political production that is dedicated to explain changes made in Roots of Brazil, in order to problematize the classifications of the text according to liberal-democratic political visions, radical-democratic or, more recently, readings that attribute positions that approach the conservative-authoritarianism of the 1930s. We intend to show that proposing an explanation of the reasons that guided the revision of the original 1936 version of this classic text requires advancing beyond the orbit of political arguments, since, rather than defining the essence of its original edition and thinking in the possibility of defining also its revised and «final» versions, what matters, above all, is to understand the logic of the movement that this revision gave to the construction of the discourse that emanates from it, once it is considered one of the key texts to interpret this country.